Existence of two weak solutions for some singular elliptic problems - Khodabakhshi, M.; Aminpour, A. M.; Afrouzi, G. A.; Hadjian, A. (Revista de la Real Academia de Ciencias Exactas, Físicas y Naturales. Serie A, Matemáticas, 2016)
In this paper, we establish the existence of at least two distinct weak solutions for some singular elliptic problems involving a p -Laplace operator, subject to Dirichlet boundary conditions in a smooth bounded domain in R N . A critical point result for differentiable functionals is exploited, in order to prove that the problem admits at least two distinct non-trivial weak solutions.